The relationship between emotional labor level and moral distress - Iskender, Mahinur Durmus; Eren, Handan; Çalışkan, Nurcan; Yılmaz, Elmas (SAGE Publications, 2023)
Background The coronavirus disease (COVID-19) pandemic has implications for health professionals. Aim The aim of this study was to explain the relationship between emotional labor levels and moral distress in health professionals during the COVID-19 pandemic using the Structural Equation Modeling (SEM) technique. Research design A descriptive and cross-sectional study was adopted. Participants and research context Data were collected between 7 February and 7 March 2021. 302 health professionals who were not on leave (annual leave, sick leave, prenatal and postnatal leave, etc.) at the time of the research and who volunteered to participate in the research were included. Research data were collected using a “Personal Information Form,” the “Emotional Labor Scale” and the “Moral Distress Thermometer.” Ethical considerations The Ethics Committee approved the study (dated 07.01.2021 and numbered 2021/1-3). The participants were informed of the study aim and written consent was obtained before completing the survey. Findings In the present study, the mediator role of emotional labor in the effect of providing service to a patient with COVID-19 and having had COVID-19 on moral distress was examined in health professionals and it was found that there was a correlation between providing service to a patient with COVID-19 and moral distress regardless of whether or not emotional labor had a role in this relationship. Conclusion In this study, the relationship between the level of emotional labor and moral distress in health professionals during the COVID-19 pandemic was evaluated with a structural equation model.
Keywords: Attitude of Health Personnel; COVID-19; Morals; Cross-Sectional Studies; Pregnancy; Surveys and Questionnaires; Humans; Female; Pandemics; 3. Good health